2015
DOI: 10.1002/ps.4053
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of electron beam irradiation on the cowpea bruchid Callosobruchus maculatus

Abstract: eBeam irradiation has very defined effects on cowpea bruchid development and reproduction. A dose of 0.06 kGy could successfully impede cowpea burchid population expansion. This information can be exploited for post-harvest insect control of stored grains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Tilton (1974) reported that the dose 500 Gy would virtually control all stored product pests by preventing their reproduction or adult emergence instead of providing acute mortality which would require much higher doses. Sang et al (2015) found that irradiation of C. maculatus adults to 2 kGy (2000 Gy) resulted in ∼50% acute mortality. They added that until 1000 Gy (1 kGy) they did not start to observe immediate deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Tilton (1974) reported that the dose 500 Gy would virtually control all stored product pests by preventing their reproduction or adult emergence instead of providing acute mortality which would require much higher doses. Sang et al (2015) found that irradiation of C. maculatus adults to 2 kGy (2000 Gy) resulted in ∼50% acute mortality. They added that until 1000 Gy (1 kGy) they did not start to observe immediate deaths.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain age‐synchronized bruchid cultures, adults (∼300, 1–4 days old) were introduced into a plastic cup containing approximately 150 cowpea seeds and were allowed to lay eggs for 2 h. Infested seeds obtained this way generally carried 5–10 eggs on each. Since cowpea bruchids feed and develop inside the seeds, precise larval and pupal developmental stages were determined as described previously: time periods required from egg laying to first, second, third, fourth instar larval and pupal stages are 156–180, 222–246, 288–312, 366–420 and 498–552 h, respectively. Hatched larvae burrow into the seeds, causing egg color change from clear to cream white.…”
Section: Methodsmentioning
confidence: 99%
“…Infested cowpea seeds in culture flasks were placed on a high‐density polyethylene (HDPE) cassette and irradiated at doses of 30, 50 and 100 Gy, respectively. These doses were selected to best reflect the protective effect of hypoxia based on previous eBeam dose response analysis . Each eBeam irradiation treatment was accompanied by an alanine dosimeter placed among cowpea seeds to be irradiated to verify the absorbed irradiation dose by a Bruker eScan spectrometer (Bruker, Billerica, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For Indian meal moth ( Plodia interpunctella ), 350 Gy γ‐ray can suppress egg hatch and larval development, but higher doses are needed to inhibit pupae and adults . Studies with cowpea bruchids ( Callosobruchus maculatus ) show that 30 Gy eBeam irradiation causes 90% mortality of fourth larvae and a dose of 60 Gy or higher is lethal to all larval stages . Although pupae are more tolerant, individuals that survived irradiation at pupal stage display smaller and more fragile ovaries in adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation